MOTHERS' KNOWLEDGE TOWARDS ORAL HEALTH OF CHILDREN AGED UP TO 3 YEARS BEFORE AND AFTER EDUCATIONAL PROGRAM - Ralitsa Bogovska-Gigova; Rositza Kabaktchieva (Peytchinski Publishing, 2021)
Purpose: To comparatively analyze the oral health-related knowledge of mothers of children aged up to 3 years before and after the "Dental Home for Children" educational program (www.dentalendom.bg) Material/methods: The study involved a group of 90 mothers of children aged up to 3 years who visited the special educational and motivational website www.dentalendom.bg and completed our survey. We compared and processed the results of the survey using 90 control questionnaires, which were completed by parents who had visited the dental office without having attended an oral health education and motivation session in advance. Results: The results obtained from the survey completed by mothers of children aged up to 3 years show that their knowledge of the importance of fluoride prevention, the risks of nighttime bottle feeding with baby formula for a long time, mistakes in feeding, and the early transmission of cariogenic bacteria increased substantially compared to the mothers who did not visit the educational website. Conclusion: The obtained positive results give us reason to believe that e-learning health education programs are useful for both mothers and children aged up to 3 years.